THE ROLE OF ENTREPRENEURSHIP EDUCATION, PARENTS AND ENTREPRENEURSHIP ORIENTATION IN INCREASING ENTREPRENEURIAL INTENTION - Melani Marsheila Handoko; Henky Lisan Suwarno (UPT Publikasi Ilmiah UNISBA, 2025)
The increasing unemployment rate, especially among college graduates, demands an effective solution to increase employment opportunities. One approach that is increasingly considered important is to foster entrepreneurial intentions among students. This study aims to evaluate the influence of entrepreneurship education, parental roles, and entrepreneurial orientation on entrepreneurial intentions, both individually and simultaneously. The approach used in this study is a quantitative method with a survey technique. Data were collected by distributing questionnaires to 95 Maranatha Christian University students who had participated in the Maranatha Entrepreneurship Day (MED) activity. This study found that entrepreneurship education and entrepreneurial orientation had a significant impact on entrepreneurial intentions. Conversely, the influence from the role of parents was not proven to be significant on entrepreneurial intentions. This study emphasizes the importance of education and entrepreneurial orientation in encouraging increased entrepreneurial intentions among students. Although the role of parents does not have a significant effect, family support can still make a positive contribution.